ANASLISIS KINERJA KEUANGAN DAN KEMANDIRIAN DAERAH KABUPATEN MOROWALI - Sitti Khalilah Yusuf; Muslimin Muslimin; Husnah Husnah (Jurnal Ilmu Manajemen Universitas Tadulako (JIMUT), 2015)
Analysis  of  Financial  Performance  and  Regional  Independence  of  Morowali  District.  In  the implementation of regional autonomy, the district government is required to be able to finance its own governance. This  indicates  that  local  governments  have  greater  responsibilities  in managing  their finances  and  increasing  their  level  of  regional autonomy.  In  this  regard,  it  is  necessary  to  conduct performance appraisal  and  financial  capacity  of  local  government  to  know  the development  of financial  management  every  year.  This  research  uses descriptive  quantitative  research  type  using ratio  analysis  tool.  The results  of  the  analysis  show  that  the  Financial  Performance  of Morowali District Government  is  seen  from  (1)  Effectiveness  Ratio  of PAD  effectiveness  of  financial performance  of  Morowali  Regency  can be  categorized  as  Not  Effective  (2)  Ratio  of  Financial Efficiency  of Region  can  categorize  Less  Efficient  (3)  Economic  Ratio  can  be categorized economically  (4)  Regional  Financial  Independence  can  be  said  to  be  very  low  with  an  instructive relationship pattern. Analisis  Kinerja  Keuangan  dan  Kemandirian  Daerah Kabupaten Morowali.  Dalam  pelaksanaan otonomi  daerah,  pemerintah  Kabupaten  dituntut  untuk  mampu  membiayai  sendiri  penyelenggaraan pemerintahan.  Hal  ini  menandakan  pemerintah  daerah  memiliki tanggung  jawab  lebih  besar  dalam mengelola  keuangan  serta meningkatkan  tingkat  kemandirian  daerahnya.  Sehubungan  hal  itu perlu dilakukan  penilaian  kinerja  serta  kemampuan  keuangan pemerintah  daerah  untuk  mengetahui perkembangan  pengelolaan keuangan  setiap  tahun.  Penelitian  ini  menggunakan  jenis  penelitian deskriptif  kuantitatif  dengan  menggunakan  alat  analisis  rasio.  Hasil analisis  menunjukkan  bahwa Kinerja  Keuangan  Pemerintah  Daerah Kabupaten  Morowali  dilihat  dari  (1)  Rasio  Efektivitas  PAD efektivitas kinerja  keuangan  Kabupaten  Morowali  dapat  dikategorikan  Tidak Efektif (2)  Rasio Efisiensi Keuangan Daerah dapat kategorikan Kurang Efisien (3) Rasio Ekonomis dapat dikategorikan ekonomis (4) Rasio Kemandirian Keuangan Daerah dapat dikatakan tergolong sangat rendah dengan pola hubungan instruktif.